Molecular Dynamics Simulation of Diffusion of Vitamin C in Water Solution - 曾建平 王爱民 贡雪东 陈景文 陈松 薛锋 (Chinese journal of chemistry, 2012)
Under different temperatures and concentrations, the diffusion of Vitamin C （VC） in water solution was exam- ined by molecular dynamics simulation. The diffusion coefficients were calculated based on the Einstein equation. The influences of temperature, concentration, and simulation time on the diffusion coefficient were discussed. The results showed that at higher temperature and lower concentration the normal diffusions appear relatively late, but the linear range of mean square displacement curves continues longer than that at lower temperature and higher concentration. At the same temperature, the normal diffusion time increases and the diffusion coefficient decreases as the simulation concentration increases. These simulation results are in good agreement with experiments. Analyses of the pair correlation functions of the simulation systems showed that hydrogen bonds are mainly formed be- tween the hydrogen atoms of VC molecules and oxygen atoms of H20 molecules, rather than between the O atoms of VC molecules and H atoms of H20 molecules. The diffusion coefficient is higher as the interaction between water molecules and VC molecules is stronger when VC concentration is lower. The water in the model systems affects the diffusion of VC molecules by the short-range repulsion of O（H20）-O（H20） pairs and the non-bond interaction of H（H20）-H（H20） pairs. The short-range repulsion of O（H20）-O（H20） pairs is greater when VC concentration is higher, the diffusion of VC is weaker. The greater the non-bond interaction of H（H20）-H（H20） pairs is, the higher the VC diffusion is. It is expected that this study can provide a theoretical direction for the experiments on the mass transfer of VC in water solution.